Answer:
Hi,
Step-by-step explanation:
p - 3q = 2
Answer:
p = 11 q = 3
Step-by-step explanation:
2p - 3q = 13
- p - 3q = 2
p = 11
p - 3q = 2
(11) - 3q = 2
-3q = -9
q = 3
Answer:
p=11 q=3
Step-by-step explanation:
subtract second from first
2p-3q=13
-p+3q=-2
p=11
plug in
11-3q=2
-3q=-9
q=3
( 8x^2 y^5) (3x y^4)
9
86
6
Answer:
Step-by-step explanation:
Given :
We know that the corresponding angles of two similar triangles are congruent.
i.e. (1)
From the given picture , we have
Then from (1),
Hence,
m < P = m < S becuase the triangles are similar.
m < P = 86 degrees
B. The 8th value
C. The 7th value
D. The mean of the 7th and 8th values